Genetic Characteristics of Multiple Copies of Tn1546-Like Elements in ermB-Positive Methicillin-Resistant Staphylococcus aureus From Mainland China - Wang, Haiping; Wu, Dandan; Di, Lingfang; Zhu, Feiteng; Wang, Zhengan; Sun, Lu; Chen, Yiyi; Jiang, Shengnan; Zhuang, Hemu; Chen, Mengzhen; Ji, Shujuan; Chen, Yan (Frontiers in Microbiology, 2022)
Objective: To determine the genetic structure of ermB-positive Tn1546-like mobile elements in methicillin-resistant Staphylococcus aureus (MRSA) from mainland China. Methods: A total of 271 erythromycin-resistant MRSA isolates were isolated from Sir Run Run Shaw Hospital (SRRSH) from 2013 to 2015. Whole-genome sequencing was performed for the ermB-positive strains, and the genetic environment of the ermB genes was analyzed. Southern hybridization analysis and transformation tests were performed to confirm the location of the ermB gene. Results: A total of 64 isolates (64/271, 23.6%) were ermB-positive strains, with 62 strains (62/64, 96.9%) belonging to the CC59 clone. The other two strains, SR130 and SR231, belonging to ST965, both harbored 14,567 bp ermB-positive Tn1546-like elements. SR231 carried three copies of identical Tn1546-ermB elements (one copy in the plasmid and double copies in two different positions on the chromosome), which had 99.99% identity to the element in the plasmid of SR130. The Tn1546-ermB elements were highly similar (100% coverage, >99.9% identity) to the element Tn6636 reported in a previous study from Taiwan. The plasmids (pSR130 and pSR231) harboring ermB-positive Tn1546-like elements were also identical to the mosaic plasmid pNTUH_5066148. Conclusion: Multiple copies of ermB-positive Tn1546-like mobile elements were found in CC5-ST965 MRSA from mainland China, showing the wide dissemination of these Enterococcus faecium-originated ermB-positive Tn1546-like elements. Molecular epidemiological study of Tn1546-like elements is essential to avoid the spreading of resistant determinants.